2014
DOI: 10.1111/mec.12980
|View full text |Cite
|
Sign up to set email alerts
|

Immune response genes and pathogen presence predict migration survival in wild salmon smolts

Abstract: We present the first data to link physiological responses and pathogen presence with subsequent fate during migration of wild salmonid smolts. We tagged and non-lethally sampled gill tissue from sockeye salmon (Oncorhynchus nerka) smolts as they left their nursery lake (Chilko Lake, BC, Canada) to compare gene expression profiles and freshwater pathogen loads with migration success over the first ~1150 km of their migration to the North Pacific Ocean using acoustic telemetry. Fifteen per cent of smolts were ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 48 publications
4
116
2
Order By: Relevance
“…GPB1 gene transcript also shows correlated expression with lncRNA in human26. Previous reports suggested that gbp1 is one of the differentially regulated immune response genes against microbial pathogens in salmon and trout927.…”
Section: Resultsmentioning
confidence: 77%
“…GPB1 gene transcript also shows correlated expression with lncRNA in human26. Previous reports suggested that gbp1 is one of the differentially regulated immune response genes against microbial pathogens in salmon and trout927.…”
Section: Resultsmentioning
confidence: 77%
“…The pathogen exposure in fish starts immediately after hatching from their protective chorions and is further enhanced during the mouth and gut opening stages and at the onset of exogenous feeding (Castro et al., 2015). Furthermore, many fish species are exposed to different and unfamiliar pathogens when they switch between fresh and salt water environments (Jeffries et al., 2014). Evidence is also growing that some fish, including non-migratory species, are being exposed to novel pathogens as a result of climate change (Crozier and Hutchings, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Collections occurred over 3 years, 2007, 2011 and 2012 at the Fraser River Chilko Lake smolt fence. In 2012, smolts were acoustically tagged and tracked (Jeffries et al 2014). 2007 was a year of very poor smolt survivalA.TissueChallengeSockeyeAtlanticChumTotalHead kidneyInjected45 (45)40 (25)45 (20)Waterborne5011645GillInjected455Waterborne4511543Liver45Injected45Spleen45Injected45Grand total275276133 684 B.TissueTotalJaundice/anemiaGill3616Head kidney3516Liver3616Spleen3113Heart3616Grand total…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, we conducted an acoustic tracking study and assessed linkages between 18 infectious agents and 50 stress and immune-related genes and migratory fate. We showed that fish with high loads of IHNv and those containing a correlated antiviral type signature (including up-regulation of MX and STAT1, the two genes overlapping with the VDD biomarkers) generally disappeared within the first 80 km of downstream migration (Jeffries et al , 2014), likely due to enhanced risk of predation by resident Bull trout (Furey, 2016). We applied the validated VDD biomarkers on the 213 smolts from the Jeffries study collected at the Chilko smolt fence in 2007, 2011 and 2012 to determine if there was evidence of viral disease in these fish (Table 1D).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation